2013
DOI: 10.1007/s11751-013-0163-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between lengthening over nail and conventional Ilizarov lengthening: a prospective randomized clinical study

Abstract: The aim of this study is to compare lengthening over an intramedullary nail to the conventional Ilizarov method with regard to percentage length increase, external fixation index, consolidation index and incidence of complications. This is a prospective randomized controlled study. Thirty-one limbs in 28 patients were included in the study; 15 were lengthened over an intramedullary nail, and 16 limbs were lengthened conventionally. The mean duration of external fixation in the lengthening over nail group was 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 15 publications
1
11
0
Order By: Relevance
“…9 However, serious complications such as deep infections, refractures, and axial deviation were still observed. 1012 …”
Section: Introductionmentioning
confidence: 99%
“…9 However, serious complications such as deep infections, refractures, and axial deviation were still observed. 1012 …”
Section: Introductionmentioning
confidence: 99%
“…However, the major criticism of this technique is the elevated risk of infection, due to the presence of external fixator fiches that may transmit superficial infection along the intramedullary nail. To minimize this possible complication, some authors recommend avoiding any contact between the fiches and nail [13, 14]. We think that avoiding any contact between the fiches and nail is very challenging, although in some cases it can be achieved.…”
Section: Discussionmentioning
confidence: 99%
“…However, the concomitant use of an intramedullary nail, such as with tibial LON, can act as a strong resistance to the deforming forces, minimizing axial deviations compared with the classic Ilizarov method. Some studies [2,3,15,20,21] compared the classic Ilizarov method with the LON technique and showed that axial deviation occurred in 4% to 13% of tibias with the classic Ilizarov method, whereas it was 0% to 2% with the LON technique. However, Kim et al [8] reported that they observed 20 segments (14%) that showed valgus angulation with a mean of 10°using the LON technique.…”
Section: Discussionmentioning
confidence: 99%